Preparing Law Students for Practice: A Non-Verbal Developmental Skill Approach - Desan Iyer (Obiter, 2019)
The article will commence with a brief overview of non-verbal communication, analyse its characteristics, and then move onto its importance to the legal sector (more specifically in legal practice) and finally will focus on the use of non-verbal communication in the classroom. The article seeks to address the grey area that currently exists within the current legal framework with the objective of introducing non-verbal practice into law curriculums in South Africa. As a way forward, it will become evident that there is a strong need for robust practical and skills emphasis in most law programmes, and such interrogation should ultimately prepare graduates for practice. The study of non-verbal communication amalgamated with traditional legal skills would go a long way to producing law graduates who have both a systematic and coherent body of knowledge, and a high level of cognitive and generic skills; together these will pave their way for successful practice.